Post-Truth Law Analysis of the Protection of Privacy Rights in Cases of Digital Defamation Dissemination in Indonesia - Judijanto, Loso; Ahmad, Ahmad; Djuhrijjani, Djuhrijjani; Furqon, Wahyul; Rohaya, Nizla (The Easta Journal Law and Human Rights, 2025)
This paper analyzes the protection of privacy rights in Indonesia in the context of digital slander dissemination, framed within the post-truth era. Using a normative juridical analysis, this study evaluates the adequacy and limitations of Indonesia's legal framework, particularly focusing on the Law on Electronic Information and Transactions (ITE Law), in addressing digital defamation. The rise of the post-truth era, characterized by the spread of misinformation and subjective narratives, has exacerbated the challenges in safeguarding privacy rights online. The paper examines legal provisions, case law, and practical enforcement mechanisms to assess how well privacy rights are protected in digital slander cases. Findings highlight the gaps in the current legal framework, including unclear definitions and enforcement challenges. The study also explores the role of social media platforms and suggests potential legal reforms to strengthen privacy protections and hold digital platforms accountable for harmful content. Ultimately, this paper calls for more robust legal definitions, improved law enforcement, and stronger platform accountability to better protect privacy in the digital age.